Modification of perpendicular magnetic anisotropy and domain wall velocity in Pt/Co/Pt by voltage-induced strain - Shepley, P.M.; Rushforth, A.W.; Wang, M.; Burnell, G.; Moore, T.A. (Nature Publishing Group, 2015)
The perpendicular magnetic anisotropy Keff, magnetization reversal, and field-driven domain wall velocity in the creep regime are modified in Pt/Co(0.85–1.0 nm)/Pt thin films by strain applied via piezoelectric transducers. Keff, measured by the extraordinary Hall effect, is reduced by 10 kJ/m3 by tensile strain out-of-plane ez5931024, independently of the film thickness, indicating a dominant volume contribution to the magnetostriction. The same strain reduces the coercive field by 2–4 Oe, and increases the domain wall velocity measured by wide-field Kerr microscopy by 30-100%, with larger changes observed for thicker Co layers. We consider how strain-induced changes in the perpendicular magnetic anisotropy can modify the coercive field and domain wall velocity.